A tenth-century Islamic manuscript from Kairouan, Tunisia - Brockopp, Jonathan E. (MAVCOR journal, 2022)
A parchment bifolio from the Kairouan collection presents a mystery. But like pottery in an archeological dig, this fragment is in situ, and clues to the identity of the author, the text, and the community of scholars that wrote and preserved it, are found in the rich context of this unique collection. Together, these manuscripts bear witness to a fascinating history of literary and cultural production, not only in North Africa, but in the broader Islamic world of the ninth and tenth century.